2015
DOI: 10.1113/ep085238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prolonged sitting on lower and upper limb micro‐ and macrovascular dilator function

Abstract: Sedentary behavior in the workplace and increased daily sitting time are on the rise; however, studies investigating the impact of sitting on vascular function remain limited. Herein we hypothesized that 6 hours of uninterrupted sitting would impair limb micro- and macrovascular dilator function and this impairment could be improved with a bout of walking. Resting blood flow, reactive hyperemia to 5 min cuff occlusion (microvascular reactivity) and associated FMD (macrovascular reactivity) were assessed in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
213
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(245 citation statements)
references
References 46 publications
20
213
6
1
Order By: Relevance
“…Our previous findings (19,20) and findings from others (15,26) that sitting causes endothelial dysfunction in the leg, but not the arm, fuel the idea that increased susceptibility of the leg vasculature to atherosclerosis may be, in part, attributable to the direct detrimental effects of prolonged sitting on that vasculature. Strategies such as fidgeting can offset the decay in leg blood flow and shear stress during sitting, thus preventing the consequent impairment of endothelial function and potentially providing important vascular benefits in the long term.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Our previous findings (19,20) and findings from others (15,26) that sitting causes endothelial dysfunction in the leg, but not the arm, fuel the idea that increased susceptibility of the leg vasculature to atherosclerosis may be, in part, attributable to the direct detrimental effects of prolonged sitting on that vasculature. Strategies such as fidgeting can offset the decay in leg blood flow and shear stress during sitting, thus preventing the consequent impairment of endothelial function and potentially providing important vascular benefits in the long term.…”
Section: Discussionsupporting
confidence: 57%
“…Along these lines, we (19,20) and others (15,25) have observed that during prolonged sitting, there is a marked reduction in blood flow and shear stress in the lower extremities that subsequently leads to leg endothelial dysfunction. We recently conducted a study designed to prevent the reduction in leg blood flow and thus shear stress during prolonged sitting with local heating of the foot (20).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Second, habitual sedentary time was not associated with skin microvascular function. This may be explained by frequent transient interruptions of habitual sedentary behavior by walking and/or standing, in such a way that detrimental effects did not appear 87,88 . Such interruptions have also been shown to be beneficial for cardiovascular risk 89 .…”
Section: Main Findings and Their Interpretationmentioning
confidence: 99%